Manajemen Peserta Didik di Lembaga Pendidikan Buddha: Pembinaan Disiplin, Karakter, dan Evaluasi - Gunawan, Adi W.; Angela, Shelfia; Fendy, Fendy; Astika, Ria (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This research aims to discuss the basic concepts of student management that briefly summarizes discipline, character, and evaluation of student learning outcomes. The type of research used in this study is library research. By using library research methods, it is hoped that this study can make a significant contribution to the understanding of student management in Buddhist educational institutions, as well as provide recommendations for better practices in developing discipline and character in the future. The results of the research show that student management plays a crucial role in educational institutions, considering that students are the primary source of input, process, and output of education. Effective management will contribute to the improvement of overall educational outcomes. By optimizing student management, as well as nurturing discipline, character, and holistic evaluation, educational institutions can shape individuals who are not only academically intelligent but also possess high morals and ethics. The application of Buddhist principles in student management has proven effective in enhancing discipline, character, and student evaluation outcomes, and educational institutions are vital in supporting the achievement of educational goals, curriculum, institutional objectives, and national education.